Characterization of Definitive Regulatory B Cell Subsets by Cell Surface Phenotype, Function and Context - Neu, Savannah D.; Dittel, Bonnie N. (Frontiers in Immunology, 2021)
Regulatory B cell or “Breg” is a broad term that represents the anti-inflammatory activity of B cells, but does not describe their individual phenotypes, specific mechanisms of regulation or relevant disease contexts. Thus, given the variety of B cell regulatory mechanisms reported in human disease and their animal models, a more thorough and comprehensive identification strategy is needed for tracking and comparing B cell subsets between research groups and in clinical settings. This review summarizes the discovery process and mechanism of action for well-defined regulatory B cell subsets. These include IL-10 producing plasmablasts/plasma cells and B cell IgD low (BDL) that maintain homeostasis of CD4+Foxp3+ T regulatory cells (Treg). We discuss the importance of conducting thorough B cell phenotyping along with mechanistic studies prior to defining a particular subset of B cells as Breg. Since virtually all B cell subsets can exert regulatory activity, it is